Labor Geographies: Workers and the Landscape of Capitalism - Zonderman, David A. (Labour / Le Travail, 2003)
The article reviews the book "Labor Geographies: Workers and the Landscape of Capitalism," by Andrew Herod.
Keywords: BOOKS – Reviews; HEROD; Andrew; Industrial relations; LABOR Geographies: Workers & the Landscape of Capitalism (Book); Nonfiction